ADVANCE AND DEVELOPMENT OF CHAOTIC OPTICAL COMMUNICATIONS: A REVIEW - Mohamed Khudhair Al-Gburi; Ibrahim A. Murdas (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The chaotic optical communication system is a new communication system that uses optical chaotic waveform to transition the data at a high bit rate. Its probable applications include secure communications and wideband communications. The semiconductor lasers are well suited for chaotic optical communications systems because the internal laser oscillation is easy to interfere with a field of optical injection or optical feedback. Chaotic optical communication is a hopeful technique for improving the privacy and security of communications networks. It uses synchronized chaotic emitters and receiver lasers for encoding and decoding the data at the hardware level. High-speed communication has made extensive use of optical communications reliant on semiconductor lasers, which are known for their wide spectrum, low power consumption, and no constraints of electromagnetic spectrum. With the chaotic optical communication's present development phase. In this paper, we review the basic technology of chaotic optical communication and research progress. We will first look at several component-based nonlinear strategies for creating chaos. Next, we focus on enhancing security, developing chaotic optical communication transmission capacity, optical chaotic synchronization, and broadband chaotic communication. We conclude by discussing the obstacles and opportunities of chaotic optical communications.